1985
DOI: 10.1021/jm00383a024
|View full text |Cite
|
Sign up to set email alerts
|

3-Amino-.beta.-carboline derivatives and the benzodiazepine receptor. Synthesis of a selective antagonist of the sedative action of diazepam

Abstract: Seven 3-N-substituted derivatives of 3-amino-beta-carboline were synthesized and their affinities for the benzodiazepine receptor were assessed in vitro. Two compounds, 3-(ethylamino)-beta-carboline and 3-[(methoxycarbonyl)amino]-beta-carboline (beta-CMC), showing IC50 values of 460 and 71 nM, respectively, were selected for in vivo studies. The former compound showed long-lasting proconvulsant activity in Papio papio baboons while beta-CMC was shown in mice to selectively antagonize the sedative effects of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The structure-affinity analysis suggested that the presence of a 3-position substituent (e. g. amide, ester, carbinol) and a fully aromatic ring system are optimal for BZR binding; while the tetrahydro--carbolines demonstrated considerably less affinity for BZR than their fully aromatic counterparts [79][80][81]. In accordance with this rule, Glennon et al [82] found that the DH Cs lacked the affinity for BZR, even when a 3-position ester group was incorporated into the ring of harmalan (9), the compound did not bind to BZRs [82].…”
Section: Interaction With Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure-affinity analysis suggested that the presence of a 3-position substituent (e. g. amide, ester, carbinol) and a fully aromatic ring system are optimal for BZR binding; while the tetrahydro--carbolines demonstrated considerably less affinity for BZR than their fully aromatic counterparts [79][80][81]. In accordance with this rule, Glennon et al [82] found that the DH Cs lacked the affinity for BZR, even when a 3-position ester group was incorporated into the ring of harmalan (9), the compound did not bind to BZRs [82].…”
Section: Interaction With Receptorsmentioning
confidence: 99%
“…Inverse agonist [133] 2. Prevention lethality from overdoses of pentobarbital [133] 3-HMC Reduce of pentobarbital-induced decrements in cerebral blood flow and oxygen consumption [134] 3-Ethoxy--carboline Partial inverse agonist [135][136] ZK 93423 Agonist [139] ZK 91296 Anticonvulsant [138] 3-Ethylamino--carboline Proconvulsant activity in Papio papio baboons [79] -CMC Selectively antagonize the sedative effects of diazepam [79] FG 7142…”
Section: Compounds Investigated Neuropharmacological Effectsmentioning
confidence: 99%
“…A similar result was observed by Allen et al 13 in the case of inverse agonists. 12 Thus 6-PBC 24 was treated with 98% hydrazine in the presence of ethanol at reflux to provide the carbohydrazide 38 via the method of Dodd et al 31 The carbohydrazide 38 was dissolved in concentrated aqueous HCl at 0°C followed by the addition of sodium nitrite. The isothiocyanato derivatives 42 and 43 (Scheme 2) were proposed as potential irreversible inhibitors.…”
Section: Chemistrymentioning
confidence: 99%
“…25 Thus, a solution of compound 10 in anhydrous DMF was treated at room temperature with ethoxycarbonyl isothiocyanate, and to the resulting thiourea 11, the appropriate dialkylamine and HgCl 2 were added to obtain the ethoxycarbonylguanidines 12a-i. Heating the DMF solution of the latter compounds under reflux induced a ring closure of the ethoxycarbonyl function into a triazine ring and the products obtained were identified as 2-dialkylamino [1,3,5] When the same reaction was applied to the 3-amino-6-bromo-β-carboline 18a using the secondary amine diethylamine, or to the 3-amino-6-nitro-β-carboline 18b using diallylamine, the triazino-β-carbolines 19a or 19b were obtained respectively.…”
Section: Resultsmentioning
confidence: 99%